Inventarisasi dan Identifikasi Potensi Pemanfaatan Tanaman Berkhasiat Obat di Kawasan Lereng Gunung Kawi Kabupaten Malang - Ahmad Ghulam Rosyidi; Titik Wijayanti; Erfitra Rezqi Prasmala; Diyah Ayu Widyaningrum (Pro-Life, 2024)
The slopes of Mount Kawi in Malang Regency had a unique ecosystem that stored valuable natural resources, including plants with medicinal properties. This research aimed to identify the diversity of medicinal plants on the slopes of Mount Kawi in Malang Regency, their utilization potential, habitus distribution, and the composition of plant parts used. The research method employed was observation with a descriptive-exploratory approach. The results revealed that the diversity of medicinal plant species and families on the slopes of Mount Kawi showed varying distribution patterns, dominated by the Rubiaceae and Fabaceae families. Four types of medicinal plant habitus were found: trees (31%), shrubs (41%), herbs (21%), and climbers (7%). Shrubs dominated with the most species, followed by trees, while climbers had the least. The composition of plant parts was dominated by leaves, with 16 types (38%) of the total utilized parts, followed by fruits and combinations of other parts, such as leaves and fruits. This predominance was attributed to the accessibility of leaves, their higher bioactive content, and their use in fresh form, boiled or extracted to treat various diseases.